Pre-Processing and Image Segmentation Techniques (Indian Journal of Public Health Research & Development, 2020)
image are known as image analysis. First step in image analysis is to segment an image. Image segmentationis a key step for partioning an image into several segments to find objects, borders &meaningful objects foran image. In image processing for any application when the work is done on an image, the initial step is todivide the image in order to solve the difficulty. Divided images are widely used in a multitude of differentapplications like density of tissue volumes, pathology, Satellite imaging, Extracting features & recognizingobjects, treatment planning & few computer integrated surgeries etc.This paper gives an overview of different image pre-processing techniques& image segmentation techniques.Before we do segmentation of an image, we need to pre-process an image to remove noise.
Keywords: Image segmentation, Pre-processing technique, image analysis